Trafficking in persons monitoring report: January 2009–June 2011 - Hannah Andrevski
Since 2008, the Australian Government has increased the tempo on investigating and understanding these crimes, and the Australian Institute of Criminology’s research and monitoring program is part of this effort.  The Government has introduced new legislation to crack down on trafficking slavery and servile marriages. Human trafficking is a serious but underreported problem as victims are unwilling to come forward. Since 2004 only 14 people have been convicted of people trafficking-related offences (nine of the 14 defendants were convicted of slavery offences, three of sexual servitude, one of people trafficking and one of labour exploitation). Between January 2009 and June 2011 there were 73 police investigations in Australia and 145 trafficked people entering the government’s victim support program—slightly more than in the previous period. Victims continue to be overwhelmingly from south-east Asia, one-third from Thailand alone. Authored by Jacqueline Joudo Larsen, Lauren Renshaw, Samantha Gray-Barry, Hannah Andrevski, and Toby Corsbie